Modern Ichthyofauna of Charvak Reservoir (Texas Journal of Agriculture and Biological Sciences, 2023)
he upper reaches of the Chirchik River experienced an anthropogenic impact, the main factors of which were irrigation construction (the creation of the Charvak reservoir) and the introduction of new fish species for the artificial formation of commercial ichthyofauna. Currently, in the ichthyofauna of the Charvak reservoir, we noted only 15 species of fish belonging to 6 families. Including - 5 native species. There is no fishing in the reservoir.